Ultrafine Kaolinite Removal in Recycled Water from the Overflow of Thickener Using Electroflotation: A Novel Application of Saline Water Splitting in Mineral Processing - Felipe M. Galleguillos Madrid; María P. Arancibia-Bravo; Felipe D. Sepúlveda; Freddy A. Lucay; Alvaro Soliz; Luis Cáceres (Molecules, 2023)
The presence of ultrafine clay particles that are difficult to remove by conventional filtration creates many operational problems in mining processing systems. In this work, the removal of clay suspensions has been investigated using an electroflotation (EF) process with titanium electrodes. The results show that EF is a viable and novel alternative for removing ultrafine particles of kaolinite-type clay present in sedimentation tank overflows with low salt concentrations (<0.1 mol/L) in copper mining facilities based on the saline water splitting concept. Maximum suspended solid removal values of 91.4 and 83.2% in NaCl and KCl solutions, respectively, were obtained under the experimental conditions of the constant applied potential of 20 V/SHE, salinity concentration of 0.1 mol/L, and electroflotation time of 10 and 20 min in NaCl and KCl solutions, respectively. Furthermore, the visual evidence of particle aggregation by flocculation during the experiments indicates a synergy between EF and electrocoagulation (EC) that enhances the removal of ultrafine particles of kaolinite.